Efficiency enhancement in bulk-heterojunction solar cells integrated with large area Ag nano-triangle arrays - Wu, Bo (2012)
Efficiency enhancement in plasmonic bulk heterojunction (PCDTBT:PCBM) organic solar cells (OSCs) is demonstrated with the integration of large area periodic Ag nano-triangle (NT) arrays (that were fabricated using the cost-effective, high throughput nanosphere lithography technique) in the OSC device. The improvements to the power conversion efficiency (from 4.24% to 4.52%) and to the short circuit current density (by ~12%) are attributed to an increase in exciton generation induced by the strong local E-field and the scattering generated by the localized surface plasmon resonance of the hexagonal NT arrays. These findings are validated by a range of steady state and transient optical spectroscopy and correlated with device performance data. Importantly, our work demonstrates the feasibility of integrating a simple cost-effective, tailorable and scalable nanofabrication technique with existing OSC fabrication processes.